THE ROLE OF THE SCHROTH METHOD IN THE DEVELOPMENT OF MEDICAL TOURISM IN VRNJAČKA BANJA - Savic, Aleksandar; Manic, Vladan (HEALTH CARE, 2023)
Vrnjačka Banja has a very large offer of services in all areas of tourism, especially in medical tourism. The aim of this paper is to analyze the possibility of further development of medical tourism in Vrnjačka Banja by introducing the Schroth therapy. The goal of this therapy is derotation, straightening and stabilization of the spinal column in a 3D three-dimensional plane, in order to prevent the consequences of scoliosis, which can only be removed by surgery. Bearing in mind that the success of this therapy depends on the patient’s attitude and the understanding of the physiotherapist’s demands, it is possible to implement it only with children over 10 years old, because patients must be focused both mentally and physically. Shrot exercises affect the spine in the sagittal, frontal and transverse planes. This method is particularly acceptable because it represents a non-surgical treatment with exercises aimed at achieving the balance of the entire body, taking the correct position of the body, stable posture. Results of the SWOT analysis show that not all conditions for the introduction of this therapeutic method have been met. It is necessary to continue to work on ensuring all the conditions for the introduction of shot therapy, as well as on the further development of medical tourism in Vrnjačka Banja.